Hypothalamic opsin 3 suppresses MC4R signaling and potentiates Kir7.1 to promote food consumption - Hala K. Haddad; Jonathan I. Mercado-Reyes; E. Román Mustafá; Shane P. D’Souza; C. Sean Chung; Ramses R. M. Nestor; Lauren E. Olinski; Valentina Martinez Damonte; Joshua Saskin; Shruti Vemaraju; Jesica Raingo; Julie A. Kauer; et al. (Proceedings of the National Academy of Sciences, 2025)
Mammalian opsin 3 (OPN3) is a member of the opsin family of G-protein-coupled receptors with ambiguous light sensitivity. OPN3 was first identified in the brain (and named encephalopsin) and subsequently found to be expressed in other tissues. In adipocytes, OPN3 is necessary for light responses that modulate lipolysis and glucose uptake, while OPN3 in human skin melanocytes regulates pigmentation in a light-independent manner. Despite its initial discovery in the brain, OPN3 functional mechanisms in the brain remain elusive. Here, we investigated the molecular mechanism of OPN3 function in the paraventricular nucleus (PVN) of the hypothalamus. We show that Opn3 is coexpressed with the melanocortin 4 receptor ( Mc4r ) in a population of PVN neurons, where it negatively regulates MC4R-mediated cAMP signaling in a specific and Gα i/o -dependent manner. Under baseline conditions, OPN3 via Gα i/o potentiates the activity of the inward rectifying Kir7.1 channel, previously shown to be closed in response to agonist-mediated activation of MC4R in a Gα s -independent manner. In mice, we found that Opn3 in Mc4r -expressing neurons regulates food consumption. Our results reveal the first mechanistic insight into OPN3 function in the hypothalamus, uncovering a unique mechanism by which OPN3 functions to potentiate Kir7.1 activity and negatively regulate MC4R-mediated cAMP signaling, thereby promoting food intake.